Social Enterprise and Social Entrepreneurship: Conceptual Clarity and Implication in Nepalese Context - Pathak, Resham Raj; Poudel, Bishwash Raj; Acharya, Paras (NCC Journal, 2018)
Correction: On 10/10/2025 the author name "Paras Education Acharya" was changed to "Paras Acharya".Purpose- The purpose of the paper is to communicate the concepts, focus and framework of social enterprise prevailing in international arena and recommend some of the research issue that can be contextualized in Nepalese setting for reaping growing importance of the issue.Design/Methodology/Approach- This paper is an analytic review, building on previous work.Findings- The varying definitions of social enterprise is found not an abnormal phenomenon as it differs according to author’s perception and context in which research is conducted. However, the generic ingredient of the concept of social enterprise is to create a positive and sustainable social impact which I believe is more powerful than promotional campaign and neuromanagement.Research limitation/Implication - The research paper helps to disseminate the diverse viewpoints on social entrepreneurship/ enterprise and provokes the need for open discourse on the topic among Nepalese academicians and business community.Originality/Value- The research paper has suggested some of the research issues and models in which future research on Nepalese perspective could be conducted.NCC JournalVol. 3, No. 1, 2018, page: 143-152